THE IMPLEMENTATION OF “I CAN” CIRCUIT GAMES TO IMPROVE INDEPENDENCE AT AL-MUHAJIRIN KINDERGARTEN - Dessy Farantika; Dwi Indrawati (-, 2021)
Independence is one aspect of development in the social-emotional field that needs to be instilled from early childhood. The purpose of this research is to (1) describe the application of the I can circuit game to increase the independence of group A children at Al-Muhajirin Malang Kindergarten (2) to describe the improvement of the independence of group A children through the I can circuit game at Al-Muhajirin Malang Kindergarten. This study uses Classroom Action Research. This study uses two cycles where each cycle. The data analysis used was qualitative and quantitative analysis. The research instrument used an observation sheet. The results of this study indicate that there is an increase in children's independence starting from cycle I to cycle II.